1991
DOI: 10.1080/10473289.1991.10466910
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Pollution in Latin America and the Caribbean

Abstract: Urban Air Pollution: General Knowledge To obtain a better knowledge of urban pollution in Latin America and 1166 the Caribbean, we conducted a survey in the 32 countries of the region. The results of this survey are presented according to four groups: (1) Mexico, (2) Central America

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 1 publication
0
24
0
4
Order By: Relevance
“…One article reviews work analyzing variation in the São Paulo light-duty fleet between 1981 and 1985, during which the number of single-fuel ethanol vehicles rose from 84,000 to 500,000, and the number of singlefuel gasoline vehicles fell by 18%. 65 This change in the fuel mix coincided with reported reductions in (average or maximum) ambient SO2 and CO levels, but persistent PM10 pollution, which was attributed to fixed sources and the heavy-duty fleet. The authors discuss possible changes in O3 production rates due to the presence of aldehydes in the air, which they list in Table 3 to be largely invariant with time for various intervals studied.…”
Section: S11mentioning
confidence: 90%
“…One article reviews work analyzing variation in the São Paulo light-duty fleet between 1981 and 1985, during which the number of single-fuel ethanol vehicles rose from 84,000 to 500,000, and the number of singlefuel gasoline vehicles fell by 18%. 65 This change in the fuel mix coincided with reported reductions in (average or maximum) ambient SO2 and CO levels, but persistent PM10 pollution, which was attributed to fixed sources and the heavy-duty fleet. The authors discuss possible changes in O3 production rates due to the presence of aldehydes in the air, which they list in Table 3 to be largely invariant with time for various intervals studied.…”
Section: S11mentioning
confidence: 90%
“…Much of those problems are a result of rapid and disorderly urban growth and industrialization, phenomena that often are not accompanied by programs aimed at protecting the environment [4][5][6]. For decades air pollution has been associated with certain adverse effects on the health of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reaffirmed air pollution as a major cause of hospitalization and death in Brazil and other Latin America cities 1,2,3,4,5,13,14,15,16,17,18,19,20,21,22 . Furthermore, the estimates are generally quite conservative.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a growing body of studies in developing countries has also shown that air pollution exerts great pressure on the environment in these areas, with a large potential impact on the population's health, especially in major urban areas 2,3,4,5 .…”
Section: Introductionmentioning
confidence: 99%